Forecasting corn production in Serbia using ARIMA model - Ilic, Ivana; Jovanovic, Sonja; Jankovic-Milic, Vesna (Ekonomika poljoprivrede (1979), 2016)
Agricultural crop production is closely related to climate, as a decisive success factor. Temperature fluctuations and changes in the volume of precipitation are the main factors affecting the growth and development of crops, and, ultimately the quantity produced. Corn is the most common crop necessary to provide for domestic needs, and a strategic product for export. Production of corn in the period from 1947 to 2014 in Serbia had an oscillatory trend, with significant jumps and falls in production. The subject of this paper is the forecasting of future trends in corn production in Serbia. Building on the subject, the purpose of this paper is to create the model for forecasting future corn production and establishingits trends.